EFEKTIFITAS NAFAS DALAM UNTUK MENINGKATKAN ARUS PUNCAK EKSPIRASI (APE) PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK - Endrian MJW; Elsye Maria Rosa (Universitas Muhammadiyah Yogyakarta, 2016)
Background: Global Initiative for Obstructive Lung chroniic Disesase (GOLD) estimated that Chronic Obstructive Pulmonary Disease (COPD) as the 6th leading cause of death in 1990 and would rise to the cause of the 3 in 2020 worldwide. COPD resulted in patients getting the respiratory system could be evidenced by a decrease in peak expiratory flow (APE), and caused respiratory function disorder so deep breathing exercises would help to boost the peak expiratory flow (PEF). Purpose: The research wanted to know affectivity of slow deep breathing exercised in increasing of peak expiratory flow in COPD patient.Methods: The researched used quasi experiment with two group pre and post test design. The responden tof this research was 50 patients of COPD in Ciamis Hospital from April to May 2015 which was gotten by simple randomization. The writer used primary data was taked from measured of peak expiratory flow at slow deep breathing groups.Results: The statistical analysis used paired t test and independent t test. Paired t test with α 95% finding indicated that slow deep breathing were effective to increasing of peak expiratory flow (p value 0,0000,05), and the analysis mean of two groups by independent t test with α 95% finding indicate that slow deep breathing as not effective to increase peak expiratory flow of COPD bronchiale patient (p value 0,3710,05.). Conclusion: this research was stated that slow deep breathing exercised was important in rehabilitation of COPD patient to increase peak expiratory flow, but intervention group was not better than control group. Keywords: COPD, Slow Deep Breathing, Peak Expiratory flow (PEF).